Exploring students’ perceptions of private mathematics tutoring in three countries - Masitah Shahrill; Farida Nurhasanah; Sahar Abbas Ibrahim; Rully Charitas Indra Prahmana; Daniel Asamoah; Haryani Mohammad; Ai Len Gan (Jurnal Infinity, 2023)
This descriptive quantitative study explored secondary school students’ reasons for receiving or not receiving private mathematics tutoring. It also explored the prevalent teaching methods private mathematics tutors use. A questionnaire was adapted to collect data from 1,309 Year 7 to Year 12 students (ages 11 to 17 years) in three countries: Brunei, Indonesia, and Iraq. The results highlight that students may receive private mathematics tutoring to pass national examinations and improve examination scores. Teachers also adapt to teaching approaches that enable students to achieve these teaching and learning goals. This study provides an initial understanding of the common reasons and teaching methods used in private mathetics tutoring across different contexts that prioritise high-stakes examination culture. The results provide implications for how private mathematics tutoring can be used to support effective teaching and learning compared to the high-stakes reasons it seems it promotes. The results also accentuate the need for families and other stakeholders to reconsider private mathematics tutoring as an opportunity to remediate the challenges students encounter in their normal classroom instruction to improve student learning.